Detection and genotyping of human papillomavirus virus (HPV): a comparative analysis of clinical performance in cervical and urine samples in Chilean women - Buchegger, Kurt (Int J Clin Exp Pathol, 2018)
Human papillomavirus (HPV) is the most common sexually transmitted infectious agent and is the main cause of cervical cancer (CC). In Chile, CC is the second leading cause of death by cancer in women aged 20-44 years, four times higher than in developed countries. Currently, the detection of HPV infection using a cervical brush is recommended; however, this is an invasive procedure that many women try to avoid. The aim of this study was to evaluate the clinical performance of a self-collected, urine-based HPV detection method using conventional PCR followed by a reverse line blot. A PCR-based HPV genotyping was performed on 190 paired cervical and urine samples from gynecological exams at public health centers in the Araucania Region, Chile. HPV DNA detection and genotyping were performed by PCR and reverse line blot assay. Carcinogenic HPV types were present in 64.7% and 65.8% of the cervical and urine samples; the infection rates of HPV16 were 34.7% and 33.2%, respectively. The overall percent agreement between carcinogenic HPV detection in cervical and urine samples was 73.7%, with a moderate concordance rate of carcinogenic HPV detection (kappa = 0.42). Clinical sensitivities for cervical and urine-based sampling methods to diagnose cervical intraepithelial neoplasia 2/3 (CIN2/3) by histology were 93.4% and 90.2%, respectively. These results suggest that both cervical brush and urine-based sampling show a good clinical performance in the detection of HPV infection. The urine-based sampling method represents a valuable alternative with a great impact on public health, allowing increased cervical cancer screening coverage among women who do not undergo pelvic examinations.